THE EFFECT OF LONGSTORAGE AT ROOM TEMPERATURE TO THE QUALITY OF SEAWEED (Eucheuma cottonii) JAM WHICH FORTIFIED Chlorella Sp.POWDER - Nur Hamdani; Syahrul Syahrul; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This study aims to determineof long storage at room temperature to the quality of seaweed(Eucheuma cottonii)jamwhich fortifiedChlorella sp.powder. The method used in this research is experimental method with Randomized Block Design (RBD) non factorial, the treatment is different concentration of Chlorella sp. powderthat is C0 (0 gr of Chlorella sp. powder) as a control, C1(1 gr ofChlorella sp. powder) and C2 (1.5 gr ofChlorella sp. powder), while as a group is a long storage, which is H1 (0 day), H2 (10 days), H3 (20 days), and H4 (30 days), by using a glass bottle. The tested parametersare organoleptic (appearance,odor, texture and flavor),chemical analysis (water and protein content) and Total plate count (TPC). The results showed that the effect of long storage at room temperature to the quality of seaweed(Eucheuma cottonii) jam which fortified Chlorella sp. powder give a real effect at 95% confidence level against organoleptic (appearance 7.02%, odor 6.80%, texture 6.84%, and flavor 6.94%), chemical analysis(water content 31.08 %, protein content 6.26%) andTotal plate count4.10 cfu/g, and can be accepted by consumers with the best storage durationis H0 - H10 at room temperature storage.  Keywords: jam, seaweed, storage, Chlorella sp